The impact of regulatory action on the co‐prescribing of renin–angiotensin system blockers in UK primary care†. Issue 7 (11th May 2017) - Allen, Craig; Donegan, Katherine
Abstract: Purpose: The aim of this study was to assess the impact of regulatory action taken in June 2014 on the co‐prescribing of renin–angiotensin system (RAS) blockers in UK primary care. Methods: RAS blocker prescriptions, issued between 01/01/2009–30/06/2015, were extracted from the Clinical Practice Research Datalink to estimate the quarterly prevalence (number of patients with at least one co‐prescription) and incidence (number of patients first receiving a RAS blocker co‐prescription) of co‐prescribing. Two different RAS blockers prescribed on the same day constituted a co‐prescription. Results: A total of 880 364 patients were prescribed a single RAS blocker during the study period. Prevalence of co‐prescribing increased from 4812 patients per million person‐years in Q1 2009 to 4865 in Q1 2010. A reduction then occurred decreasing to 2901 patients per million person‐years in Q2 2014 when the EU review concluded and continued to decrease thereafter despite a continued increase in the prevalence of prescribing of a single RAS blocker. Incidence of new co‐prescribing decreased from 454 patients per million person‐years in Q1 2009 to 159 in Q2 2014, but remained relatively constant at 119 patients per million person‐years on average after the EU review concluded. A total of 96% of co‐prescriptions were for an ACE inhibitor + ARB, and 4% accounted for an ACE inhibitor or ARB + renin inhibitor. Conclusions: Recently, there has been a decrease in the prevalence and incidence of RAS blocker co‐prescribing. Reassuringly, overall co‐prescribing reduced in line with recommendations, although there was a decreasing trend prior to this likely due in part to prior publication of the data used in the EU review. © 2017 Crown copyright. Pharmacoepidemiology and Drug Safety © 2017 John Wiley & Sons, Ltd.